2018
DOI: 10.1177/0144598718779212
|View full text |Cite
|
Sign up to set email alerts
|

Methane adsorption characteristics and its influencing factors of the medium-to-high rank coals in the Anyang-Hebi coalfield, northern China

Abstract: The variation of coal rank in the Anyang-Hebi (Anhe) coalfield has the phenomenon of anti-Hilt law, which makes the coalfield distinctive for coalbed methane exploration research. The methane adsorption characteristics and influencing factors of the medium-to-high rank coal samples of the Shanxi Formation in this coalfield were analyzed. The results indicate that the Langmuir volume (V L) of coals in the shallow western part of the Anhe coalfield is generally higher than that in the deep eastern part. The coal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 29 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…The pores and fractures in the inertinite group are not developed, and are more hydrophilic than the vitrinite. The increase of water content will reduce the ability of coal reservoir to adsorb methane (Chen et al, 2018; Zhao et al, 2018). The vitrinite content in the study area is 15.1–49.7%, and the inertinite content is 35.1–73.6%.…”
Section: Resultsmentioning
confidence: 99%
“…The pores and fractures in the inertinite group are not developed, and are more hydrophilic than the vitrinite. The increase of water content will reduce the ability of coal reservoir to adsorb methane (Chen et al, 2018; Zhao et al, 2018). The vitrinite content in the study area is 15.1–49.7%, and the inertinite content is 35.1–73.6%.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, as a result of the restriction of the diffusivity and the desorption kinetics of methane molecules on the inner surface of the micropore, methane desorption will certainly control the succeeding procedure of gas production. , A lot of previous studies on the adsorption and desorption characteristics of gases in coal are mainly based on isothermal adsorption equations, including the Langmuir isothermal adsorption equation, which can provide essential recommendations for gas production assessment and mathematical modeling. Nevertheless, the obtained isothermal information can just supply macroscopic and static information and disregard the dynamic procedure during gas adsorption and desorption. Do and Wang measured adsorption and desorption equilibrium data on activated carbon and discovered the existence of the adsorption delay phenomenon. The outcomes of their research showed that adsorption on the pore surface of activated carbon is heterogeneous, which causes the truth that the adsorption of gases does not take place instantly and it takes some time to get to adsorption-desorption equilibrium, in which case the time consumption of gas adsorption and desorption is close to gas diffusion.…”
Section: Introductionmentioning
confidence: 99%